Development of a recipe for a multicomponent mixture «Solodok +» to improve the consumer properties of bakery products - Bilyk, Olena; Bondarenko, Yuliia; Kochubei-Lytvynenko, Oksana; Burchenko, Liudmila (My University, 2021)
The object of research is the technology of bakery products enriched with a mixture of germinated grains of wheat, corn, barley and oats. Investigated problem: The problem of using a mixture of germinated grains is the formation of a closure sticky crumb in baked goods with a mixture. The reason for this is the high activity in the mixture of amylolytic and proteolytic enzymes. The solution to the problem consists in the developed multicomponent mixture (MM) to improve the consumer properties of bakery products, the formulation of which includes 15 % of the flour mass of the germinated grain mixture. Main scientific results: On the basis of experimental studies, the formulation of the “Solodok+” multicomponent mixture has been developed. The mixture contains: chicory inulin, dry milk whey enriched with Mg and Mn, apple pectin, phosphatide concentrate, enzyme preparation Deltamalt FN-A 50 and ascorbic acid. The optimal dose of the “Solodok+” MM for bakery products is 2.5 % by weight of flour. The area of practical use of the research results: “Solodok+” MM is recommended to be used in the production of bakery products enriched with sprouted grains at enterprises of the bakery industry of various capacities. An innovative technological product: “Solodok+” MM helps not only to reduce the stickiness of the crumb, improve its porosity, increase the volume of products, but also lengthen the freshness of unpackaged products. Scope of application of the innovative technological product: Bakery products with a mixture of sprouted grains and “Solodok+” MM have increased nutritional value, high consumer properties and are intended for a wide range of consumers.
Keywords: mixture of germinated grains; multicomponent mixture; bakery products; consumer properties; кафедра технології хлібопекарських і кондитерських виробів; кафедра технології молока і молочних продуктів; суміші пророщених зерен; суміш багатокомпонентна; хлібобулочні вироби; споживчі властивості